Two New phytoecdysteroids from sphenocentrum jollyanum pierre root (2019)
The crude methanol extract of Sphenocentrum jollyanum root exhibited 98% and 80% antimicrobial activity against Aspergillus fumigatus Pinh and Vancomycin resistant enterococcus (VRE) at a concentration of 200 μg/mL, with ICso 11.45 and 12.95 μg/mL, respectively. The ethyl acetate fraction of methanol extract showed in-vitro antimicrobial activity against A. fumigatus Pinh at 83% with ICso of <8 μg/mL. The phytochemical investigation of ethyl acetate fraction yielded six compounds, which were identified by their NMR, IR and MS spectral analyses as two new phytoecdysteroidal glycosides Sphenocentroside A (1), and NUSART Sphenocentroside B (2), and four known phytoecdysteroids: polypodoaurein (3), polypodine B (4), ecdysterone (5), and 20, 26-dihydroxyecdysone (6).